Off-the-shelf implant to bridge a urethral defect: multicenter 8-year journey from bench to bed - Vythilingam, Ganesh; Larsson, Hans M.; Wei, Sien Yeoh; Mohd Zainuddin, Saiful Azli; Engelhardt, Eva Maria; Sanmugam, Anand; Yau, Lun Ch'ng; Yi, Xian Foong; Wak Harto, Muhd Khairul Akmal; Pinnagoda, Kalitha; Chen, Hui Cheng; Radzi, Rozanaliza; et al. (Elsevier, 2025)
Objective: To engineer an acellular mesh to reconstruct the urethra to replace the current surgical practice of using autologous tissue grafts. Cell based approaches have shown progress. However, these have been associated with high costs and logistical challenges. Materials and Methods: Acellular meshes were engineered using liquid collagen. They underwent in vitro, mechanical and bench testing by surgeons. Sixty-nine male New Zealand rabbits were used to refine the design. The final prototype based on the TissueSpan patented technology was then implanted again in a 2 cm long urethral defect in 9 rabbits and in a 4 cm long defect in 6 dogs. Results: The TissueSpan technology platform allows for the manufacturing of tubular and rectangular meshes in different diameters and thicknesses. The tubular mesh acted as physical conduit to gap the urethral defect with a patent urethra demonstrated after 1 month in both animal models. The mesh was absorbed within 1-3 months. Spontaneous urothelial coverage of the mesh and smooth muscle cell migration into the surgical area was demonstrated even in a 4 cm long urethral defect. A first in man clinical trial was subsequently initiated. Conclusion: The acellular mesh may have the potential to be an off-the-shelf product for substitution urethroplasty. Its mechanical properties allow surgeons to easily create a physical conduit while its material properties favor tissue remodeling. A large-scale clinical trial is still required to further confirm the safety, performance, and patient benefit of this new medical device.